Colchicine overdose: Report of two cases (秋水仙碱中毒两例病例报告) - LI Xuejing (李雪晶); YANG Jun (杨军); TANG Ziren (唐子人); SHEN Luhui (沈露晖) (Journal of International Translational Medicine Limited, 2021)
Colchicine is an alkaloid derived from Colchicum automnale and Gloriosa superba, which becomes more widely used for the treatment of acute gouty arthritis, but its therapy dose is near to the poisoning dose. This paper reported two cases of colchicine overdose with different prognosis. Even the continuous veno-venous hemofiltration have been done to decrease the serum concentration of colchicine, the prognosis could not be reversed in case one. Due to the lower serum concentration of drug, case two had the better prognosis. The coagulopathy and elevated liver enzyme had been found in both cases. A significant leukocytosis with thrombocytopenia was observed in case one. The colchicine is a high poisonous drug, over dose of which has a bad prognosis and rapid change of clinical status. The clinical doctors should take it seriously. (秋水仙碱是从秋水仙和桂花中提取的生物碱, 广泛应用于急性痛风性关节炎, 但使用剂量接近于中毒剂量。本文报告了两例秋水仙碱中毒病例, 其中一例经连续血液滤过降低了血清秋水仙碱浓度后, 预后依然不可逆转; 第二例由于血药浓度相对较低而预后更好。两例均见凝血功能障碍和肝酶升高, 其中病例一有明显白细胞增多伴血小板减少。秋水仙碱药物不良反应明显, 服用过量者预后差且病情进展快, 临床应用需小心谨慎。)